Penerapan Kaidah Al-Masyaqqah Tajlibu At-Taysir dalam Akad Transaksi Jual Beli Online (E-Commerce) - Nur Azizah; Siti Maulidya Putri; Lahmudinur Lahmudinur (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The gap between classical Islamic jurisprudential sale contracts and digital transactions has generated legal issues concerning contract validity, object clarity, and rights protection in e-commerce. This study focuses on the application of the fiqh principle Al-Masyaqqah Tajlibu At-Taysir as the foundation of Islamic legal flexibility in online buying and selling practices. The research employed a qualitative method with a library research approach through the examination of fiqh muamalah and qawaid fiqhiyyah literature. The findings indicate that online transactions present various forms of masyaqqah, including the absence of direct interaction between sellers and buyers, the potential for gharar due to limited product verification, delivery delays, and the risk of product mismatch. The principle of Al-Masyaqqah Tajlibu At-Taysir is applied through the recognition of electronic contracts, product descriptions, review systems, shipment tracking, and return and refund mechanisms as forms of taysir that preserve transactional convenience without neglecting sharia principles. Transaction validity is determined by the fulfillment of mutual consent, clarity, honesty, and justice. This study concludes that Islamic law possesses the capacity to adapt to the development of digital transactions through the application of fiqh principles while maintaining fundamental sharia values.